Knowledge and awareness on disaster management among medical professionals of a selected public and private medical college hospital - Rahman, Atoshi Bazi; Chaklader, Mainul Alam; Muhammad, Faisal (International Journal of Advances in Medicine, 2018)
Background: Disaster causes widespread destruction, disrupting people’s lives and causing human suffering with communities finding it difficult to cope. When the disaster occurs, human beings may not have the power to stop it from occurring, nevertheless they may have the power and ability to adapt or minimize the impact of the disaster on their lives. This study was aimed to assess the level of knowledge and awareness on disaster management among medical professionals. Methods: A cross-sectional study was conducted among the medical professionals from two selected medical college hospitals in Dhaka city of Bangladesh from January to April 2017. A total of 120 samples were selected purposively using two stages sampling technique. The data was collected using self-administered semi-structured questionnaire and was analysed using SPSS 20.0 version. Results: In this study half 60 (50.0%) of the study participants were in the age group 20-30 years and about 77.5% of the study participants were Muslims. About 64.2% of the study participants had less than 11 years of professional experience. Only 10 (8.3%) of the study participants had attended training on disaster management. About 30.0% of the study participants had good level of knowledge and only 49.2% had high level of awareness. Conclusions: The findings revealed that most of the study participants had not attended any training on disaster management. It also reported that the majority of the study participants had poor level of knowledge. Evacuation exercises need to be done for the entire hospital at least twice a year.